Assessment Of Menopausal Symptoms And A I Iitude, And Intervention Study On Knowledge Of Hormone Replacement Therapy Among Peri Menopausal Women Seen At Outpatient Department (Krk)&Obstetrics And Gynaecology Clinic (O&G), Husm. - Nik Kazim, Nik Harlina Roza (2001)
This study was designed to examine HRT users' attitudes and knowledge of menopause and HRT, their menopausal symptoms, comparing that with a control group (non HRT user) and to examine the effectiveness of counseling intervention in educating the non HRT user.